1982
DOI: 10.1002/bjs.1800691108
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of gastric emptying after gastric bypass surgery using radionuclides

Abstract: The pattern of gastric emptying has been assessed after gastric bypass surgery using a double isotope technique for measuring solid and liquid emptying with a scintillation camera. Eleven control subjects and 12 patients, 12 months post-gastric bypass, were studied. Stomal and gastric pouch size were assessed at endoscopy. Solid emptying was slower and liquid emptying was more rapid after gastric bypass surgery. Initial rapid emptying of solid occurred in the 4 patients with the smallest pouch diameters. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
7

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 12 publications
3
63
0
7
Order By: Relevance
“…Naslund et al [5] observed delayed emptying after gastroplasty and after gastric bypass. Horowitz et al [22] found a delay in emptying for solid food after gastric bypass surgery. However, in neither of these studies, a relation between the delay in gastric emptying and weight loss could be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Naslund et al [5] observed delayed emptying after gastroplasty and after gastric bypass. Horowitz et al [22] found a delay in emptying for solid food after gastric bypass surgery. However, in neither of these studies, a relation between the delay in gastric emptying and weight loss could be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…At higher duodenal glucose loads, the maximal rate of proximal small intestinal glucose absorption is probably exceeded so that a greater length, and more distal regions, of the gut-with a higher density of GLP-1-secreting L cells-are exposed (7). Postprandial GLP-1 secretion is exaggerated after gastric bypass surgery (19), which is associated with markedly accelerated gastric emptying of nutrient liquids (20).…”
Section: Diabetesdiabetesjournalsorgmentioning
confidence: 99%
“…However, after the modified technique with near total gastric resection, rapid gastric emptying has been documented in some reports [4,5]. Other authors reported rapid emptying for liquids and slower emptying for solids after gastric bypass [6]. Few data are available in the literature concerning this topic in patients submitted to other bariatric operations.…”
Section: Introductionmentioning
confidence: 95%